The Role of Peer Play in Prosocial Behavior among Preschool Children Aged 4-6 Years - Freska Reti Therina Kefi; Fredericksen Victoranto Amseke; Anita A. Hege Udju (Kumara Cendekia, 2026)
Early childhood prosocial behavior is very important for sharing, helping, empathizing, and collaborating when playing with peers as the foundation of early childhood social development. The purpose of this study was to determine the effect of playing with peers on the prosocial behavior of children aged 4–6 years at Efata Liliba PAUD, Kupang City. This research method is quantitative with a purposive sampling technique for children aged 4–6 years. The respondents of this study were 52 children aged 4–6 years at Efata Liliba PAUD. The data collection technique used a questionnaire in the form of a scale of playing with peers and a scale of prosocial behavior. The data analysis technique was simple linear regression. The results of the study found a positive and significant effect between playing with peers on children's prosocial behavior with a coefficient of determination (R²) of 0.746, which means that the effect of playing with peers on children's prosocial behavior contributed 74.6%. The better children play with peers, the more it can improve children's prosocial behavior. It is hoped that parents and teachers will provide activities for children to play and interact socially and emotionally with peers to develop children's abilities in prosocial behavior.